Judicial Oversight: Constitutional Framework for Right to Clean and Healthy Environment in India (International Journal of Food and Nutritional Sciences, 2022)
A conducive environment is of utmost importance for human well-being, enabling physical, mental, and intellectual development within natural and built settings. Indian judges have displayed remarkable diligence in their enlightened decisions, laying much-needed emphasis towards the preservation of the environment, and adhering and addressing the requirements of individual people while keeping the future generation in their hindsight. Delving into the critical dimension of environmental justice, this study also investigates the concept the constitutional framework underpinning the entitlement to a uninfected atmosphere, considering its historical development, legal precedents, and contemporary significance. This paper briefly illuminates select cases where a precedent has been set which establishes the Right to Environment as a Fundamental Right in India, meanwhile assessing the transformative function of the Indian judiciary in developing jurisprudence related to protecting and preserving the environment. Ultimately, it underscores the crucial function of the judiciary in safeguarding environmental rights and fostering sustainability within the Indian legal landscape.